Prevalence and Associated Factors of Psychological Distress of Patients with Stroke Attending the Clinics of the National Institute of Neurology of the National Hospital of Sri Lanka, Colombo - Weerasinghe, W.M.N.N.P.; Warshawithana, C.N; Weerasekara, W.M.P.C.; Mashood, Irshad (International Journal of Medical Students, 2023)
INTRODUCTION: Stroke is the fifth leading cause of disability adjusted life years lost in Sri Lanka. A vast range of factors lead to psychological distress among stroke patients causing poor outcomes such as limitations of daily activities, poor rehabilitation outcomes, social isolation, and poor financial recovery. Nevertheless, there is a scarcity of data on this topic, in both foreign and local literature. OBJECTIVES: To assess the prevalence of psychological distress and identify the factors associated with it among the patients with stroke attending the clinics of National Institute of Neurology (NIN), National Hospital of Sri Lanka (NHSL), Colombo. METHODS: A descriptive cross-sectional study with an analytical component was conducted among 177 patients with stroke attending the clinics of National Institute of Neurology, National Hospital of Sri Lanka, Colombo who were sampled by multistage random sampling. The 10-item Kessler psychological distress scale was used to assess the psychological distress while the Barthel Index and the modified Rankin Scale were used to assess the dependence on the Activities of Daily Living (ADL) and disability status respectively. Data was collected regarding socio-demographic, behavioral, family and caregiver, stressful life events, stroke and other health related factors using a pretested interviewer administered questionnaire. Chi-square tests, simple logistic regression was used for bivariate analysis followed by multivariate analysis via binary logistic regression. Results obtained from the final regression model were expressed using odds ratios with 95% confidence intervals whilst associations with p-value < 0.05 were significant in all types of analyses. RESULTS: The mean age of the participants with stroke was 59.6 (SD 12.285) years. The prevalence of psychological distress among stroke patients was found to be 23.3% (95% CI: 16.1 - 31.9) using the validated K10 score of ≥22. During bivariate analysis, none of the sociodemographic, family and caregiver related, and stressful life event related factors were significantly associated while past personal history and family history of psychiatric disorders, frequency of engagement in physical and leisure time activities prior to the stroke event, time since the last stroke event, level of disability and dependence on ADL (p < 0.05) were found to be significant predictors of psychological distress. The results of regression identified five independent predictors with a R2 of 0.772. There, the presence of psychological distress was significantly predicted by age (b = -.134, p < 0.05), gender (b = 4.262, p = 0.05), patient being the sole source of income (b = 3.207, p < 0.05), ii level of disability (b = 2.568, p < 0.001) and past personal history of psychiatric disorders (b = 5.151, p < 0.05). CONCLUSION: The prevalence of psychological distress among patients with stroke attending the clinics of the NIN, NHSL, Colombo is high and is associated with several health and non-health related factors. A standard routine screening method should be formulated for early diagnosis of patients at risk of psychological distress supplemented by a multidisciplinary approach including psychosocial support starting from the initial out-patient management of stroke patients.